Characteristics of Hardcore Male Smokers in Taiwan: A Qualitative Study - Hui-Wen Huang; Kuang-Chieh Hsueh; Wen-Wen Li; Chih-Ling Huang (JMIR Publications, 2020)
Objectives: The purpose of this study was to explore the characteristics of hardcore smokers who were previously hospitalized. Study design: A descriptive qualitative design was used to investigate a sample of 29 male Taiwanese smokers. Methods: Male hardcore smokers were recruited at a hospital in southern Taiwan and their smoking behaviors and attitudes were explored in semistructured interviews. Inclusion criteria were: (1) smoking at least weekly or daily during the past year, (2) 100 cigarettes during the lifetime, (3) persistent smoking, or (4) at least one hospitalization. Audio-recorded interview data were analyzed using content categorization of the responses. Results: Four main themes emerged to describe characteristics of Taiwanese hardcore smokers: (1) physiological and psychological dependence, (2) no motivation to quit despite knowledge of negative health consequences, (3) social interaction and cultural norms, and (4) negative attitudes toward, but compliance with, smoking-free policies. Conclusions: The results can inform public health nurses of characteristics of Taiwanese hardcore smokers, which in turn may develop effective smoking cessation program to increase smoking cessation rate among Taiwanese hardcore smokers.